Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan di Balai Penjaminan Mutu Pendidikan DKI Jakarta - Andri Prana Joni; Syahrial Addin; Yulia Mujiaty (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine the effect of work environment and work discipline on employee performance at the Jakarta Education Quality Assurance Agency (BPMP). Work environment and work discipline are important factors that can influence employee productivity and performance effectiveness, especially in government agencies engaged in improving education quality. The research method employed is an associative quantitative approach, with data collection techniques involving a questionnaire distributed to the entire population, comprising 87 BPMP employees, using total sampling. Data testing was conducted through validity tests, reliability tests, classical assumption tests, multiple regression analysis, t-tests (partial), F-tests (simultaneous), and determination coefficients. The research results indicate that both the work environment and work discipline have a positive and significant impact on employee performance, both partially and simultaneously. A comfortable work environment and high work discipline can drive improvements in employee performance in carrying out their duties and responsibilities. This study contributes as a basis for evaluation and improvement of human resource management at the Jakarta Capital City BPMP in creating a conducive work environment and a disciplined work culture.